Fifth International Conference on Quality Software (QSIC'05)
DOI: 10.1109/qsic.2005.67
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Metamorphic Testing Methodology for Service-Oriented Software Applications

Abstract: Testing applications in service-oriented architecture (SOA) environments needs to deal with issues like the unknown communication partners until the service discovery, the imprecise blackbox information of software components, and the potential existence of non-identical implementations of the same service. In this paper, we exploit the benefits of the SOA environments and metamorphic testing (MT) to alleviate the issues.We propose an MT-oriented testing methodology in this paper. It formulates metamorphic ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…After manually studying 70 MRs reported in the literature [38,12,47,68,83,14,70,58,59,71,44], we found that 43 (61.4%) MRs are polynomial, i.e., the relations between inputs and the relations between outputs are both polynomial equations. Therefore, in this paper, we focus on inferring only such polynomial MRs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…After manually studying 70 MRs reported in the literature [38,12,47,68,83,14,70,58,59,71,44], we found that 43 (61.4%) MRs are polynomial, i.e., the relations between inputs and the relations between outputs are both polynomial equations. Therefore, in this paper, we focus on inferring only such polynomial MRs.…”
Section: Introductionmentioning
confidence: 95%
“…That is, our approach tries to find a set of parameter values that characterize the analyzed executions in the form of an MR. Furthermore, to improve the quality of MRs, our approach applies statistics based filtering to the inferred MRs. Based on our study on the literature of MRs [38,47,68,83,12,14,70,58,59,71,44], 23 (53.5%) polynomial MRs are simple polynomial MRs whose relations between inputs are linear equations and whose relations between outputs are linear or quadratic equations. Therefore, in the current stage our approach focuses on inferring these particular polynomial MRs.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue Gupta and Bajpai (2014) Chan et al (2007) proposed framework for testing SOA applications. This study is extension of Chan et al (2005). Proposed framework uses metamorphic testing approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chan et al [4] applied metamorphic relations to construct test cases for stateless web services. Li et al [10] studied unit testing problems for service orchestration.…”
Section: Related Workmentioning
confidence: 99%
“…Software built on top of the service-oriented architecture (SOA) is increasingly popular [4][14] [27], and yet testing such software remains tedious and ill-understood. In these applications, primary components are typically known as services.…”
Section: Introductionmentioning
confidence: 99%